2004
DOI: 10.4049/jimmunol.172.2.1018
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Dendritic Cell System during Mouse Ontogeny

Abstract: Based on the view that the efficacy of the immune system is associated with the maturation state of the immune cells, including dendritic cells (DC), we investigated the development and functional potential of conventional DC and plasmacytoid pre-DC (p-preDC) in spleen, thymus, and lymph nodes during mouse development. Both CD11c+ DC and CD45RA+ p-preDC were detected in small numbers in the thymus as early as embryonic day 17. The ratio of DC to thymocytes reached adult levels by 1 wk, although the normal CD8α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 43 publications
9
139
0
Order By: Relevance
“…Many studies that compared neonatal and adult mice using in vitro approaches have described deficiency or immaturity in neonatal T cell and neonatal APC function (47)(48)(49)(50). In contrast, many in vivo studies of T and B cell responses to Ag with adjuvant or viral infections have reported comparable responses in neonatal and adult mice (51)(52)(53).…”
Section: Figurementioning
confidence: 99%
“…Many studies that compared neonatal and adult mice using in vitro approaches have described deficiency or immaturity in neonatal T cell and neonatal APC function (47)(48)(49)(50). In contrast, many in vivo studies of T and B cell responses to Ag with adjuvant or viral infections have reported comparable responses in neonatal and adult mice (51)(52)(53).…”
Section: Figurementioning
confidence: 99%
“…1A). Total CD11c int/hi MHC-II int/hi CD11b int/hi DC numbers (i.e., blood-derived and skin/tissue-derived DC) (23,24) peaked at day 4 p.i. (Fig.…”
Section: Changes In the Aln And Skin Following Wnv Infectionmentioning
confidence: 99%
“…Although newborn mice have few CD11c ϩ cells and mature DC do not fully develop until 5 wk of age (35), thymus and spleen cells from newborn wild-type and Ins1 Ϫ/Ϫ Ins2 Ϫ/Ϫ mice stained with the polyclonal Ab to GAD. Thus, PAE cells were present at birth, although possibly not fully matured.…”
Section: Proinsulin Surface Staining Depends On Insulin Gene Transcrimentioning
confidence: 99%